2021
DOI: 10.1038/s41419-021-03873-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress granules, RNA-binding proteins and polyglutamine diseases: too much aggregation?

Abstract: Stress granules (SGs) are membraneless cell compartments formed in response to different stress stimuli, wherein translation factors, mRNAs, RNA-binding proteins (RBPs) and other proteins coalesce together. SGs assembly is crucial for cell survival, since SGs are implicated in the regulation of translation, mRNA storage and stabilization and cell signalling, during stress. One defining feature of SGs is their dynamism, as they are quickly assembled upon stress and then rapidly dispersed after the stress source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 155 publications
2
101
1
Order By: Relevance
“…First, stationary-phase growth, oxidative stress, glucose starvation, and cytosol acidification under stress here observed are traits that afford a suitable environment for the assembling, or level increasing, of SGs, PSGs, and PBs (Eulalio et al 2007;Buchan et al 2008;Kato et al 2011;Ramachandran et al 2011;Shah et al 2013;Wang et al 2018; Leeuwen and Rabouille 2019). Furthermore, as expected for cells accumulating SGs, and PSGs (Peters et al 2013;van Leeuwen and Rabouille 2019;Marcelo et al 2021), all strains here analyzed rebound after stress relief.…”
Section: The Membraneless Organelles Storage and Degradation Are Related To Etoh Stress: Lncrnas Also Act On These Systemssupporting
confidence: 72%
“…First, stationary-phase growth, oxidative stress, glucose starvation, and cytosol acidification under stress here observed are traits that afford a suitable environment for the assembling, or level increasing, of SGs, PSGs, and PBs (Eulalio et al 2007;Buchan et al 2008;Kato et al 2011;Ramachandran et al 2011;Shah et al 2013;Wang et al 2018; Leeuwen and Rabouille 2019). Furthermore, as expected for cells accumulating SGs, and PSGs (Peters et al 2013;van Leeuwen and Rabouille 2019;Marcelo et al 2021), all strains here analyzed rebound after stress relief.…”
Section: The Membraneless Organelles Storage and Degradation Are Related To Etoh Stress: Lncrnas Also Act On These Systemssupporting
confidence: 72%
“…The formation of stress granules is one important player in stress response, as they play an important role as mediator of protein synthesis. During SGs assembly, several key players, such as RBPs and mRNAs are sequestered into the granule preventing these components from integrating the translational machinery 12,48 . Previous evidence has also shown that SGs co-localize with several protein aggregates, which are characteristic of different neurodegenerative diseases 49 .…”
Section: Discussionmentioning
confidence: 99%
“…These are transiently formed foci that act in the triage and regulation of RNA during stress periods 11 . Recently, SGs dysregulation has been suggested to underlie the pathogenesis of several diseases, including neurodegenerative disorders 12 . SGs are dynamic structures that can have different compositions depending on the type of stress and type of cell, although RNA binding proteins (RBPs) are their main components.…”
Section: Introductionmentioning
confidence: 99%
“…SGs are membrane-less cytoplasmic compartments made of ribonucleoproteins complexes and exhibiting a liquid-like property, which allowing the rapid exchange of mR-NAs and proteins with the cytosol. The mechanisms regulating the dynamic assembly/disassembly of SGs are complex but appear to be widely conserved across species [20]. SG formation is triggered by a variety of cellular stresses including nutrients deprivation, hypoxia, heat shock, UV irradiation, oxidative and ER stresses, impaired protein degradation, and many others [21].…”
Section: Molecular Bases and Complexity Of Sg Biogenesismentioning
confidence: 99%